Liquid Soap from Nyamplung Seed Oil (Calophyllum inophyllum L) with Ketapang (Terminalia catappa L) as Antioxidant and Cardamom (Amomum compactum) as Fragrance - Senny Widyaningsih; Mochammad Chasani; Hartiwi Diastuti; Wawan Nur Fredyono (Molekul, 2018)
The non-edible oil from nyamplung seed (Callophyllum inophylum L.) has been widely used as a soap ingredient. The soap production from nyamplung seed oil with the addition of antioxidant and fragrance had been carried out in this research. Ketapang (Terminalia catappa L) fruit extract and Cardamom (Amomum compactum) were used as antioxidant and fragrance substances, respectively. The variation of concentration of antioxidant and fragrance has been carried out to obtain the high quality of soap. Characterization was done to know the quality of soap in accordance with SNI 06-4085-1996. The antioxidant activity was analyzed using DPPH (1,1-diphenyl-2-picrylhydrazyl). The results showed that the addition of 1% ketapang fruit extract and 3% cardamom fragrance exhibited the best characteristics. The antioxidant activity test showed that the IC50 value of the best antioxidant soap is 79.51 ppm, indicating that the soap is a strong category